Horns and Trumpets of the World: An Illustrated Guide - Montagu, Jeremy (Rowman & Littlefield Publishers, 2014)
Humanity has blown horns and trumpets of various makes and models, lengths and diameters since prehistoric times. In Horns and Trumpets of the World, the eminent scholar Jeremy Montagu surveys the vast range in time and type of this instrument that has accompanied everything in human history from the war cry to the formal symphony, from the hunting call to the modern jazz performance. No work on this topic offers as much detail or so many illustrations—over 150, in fact—of this remarkable instrument. Montagu’s examination starts with horns constructed from such unusual materials as seaweed, cane, and bamboo, and continues the journey of exploration through those of shell, wood, ivory, and metal. The chronological scope of Horns and Trumpets of the World is equally vast: it looks at instruments of the Bible and from the Bronze and Iron Ages respectively before diving headlong into those from the Medieval, Renaissance, Baroque, and Classical periods, and, following the Industrial Revolution, those that have appeared in the modern era. Drawing on the many instruments from the author’s own extensive collection, Montagu offers details, including measurements, at levels rarely seen in other surveys of this world of instrumentation. Horns and Trumpet of the World should appeal to not only scholars and collectors, but professional brass players and manufacturers, as well as museums and institutions with a vested interest in our musical heritage.